(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is dedicated to the researching of the individual-author’s adaptation of the fixed language means in the publicity of M. Hrushevsky. The analysis of the main types of the idioms’ structural-semantic transformation is effectuated here, the functional-stylistic and pragmatic filling are also ascertained in the article.